PENGARUH PUNISHMENT DAN REWARD TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN FIKIH KELAS VIII DI MTs AL- FATAH AMBON - Mirna Mirna (Kuttab: Jurnal Ilmiah Mahasiswa, 2021)
Abstract: The purpose of this study was to determine whether there is an effect of giving punishment and reward on improving student learning outcomes in fiqh lessons at MTs Al-Fatah Ambon. This study uses a quantitative type of research, carried out for one month starting from November 19, 2020 to December 19, 2020. The population in the study is all students in class VIII (VIII1, VIII2, and VIII3) and a sample of 30 people from all students in class VIII. taken by using random random sampling technique with research scores using a Likert scale. In measuring the instrument, the researcher used a questionnaire as many as 22 statements which were carried out using google from. Then testing was carried out using validity and reliability tests with the help of SPSS version 22. After obtaining data from the questionnaire results, the researchers analyzed the data with linearity and normality tests using SPSS version 22 assistance. The variable for fiqh learning outcomes was in the form of midterm exam scores for the 2019-2020 school year. . The data analysis technique used to test the researcher's hypothesis was the F test. The results showed that; (1) There is a positive and significant effect of giving punishment on student learning outcomes with the value of the results of the hypothesis test (t test) with a value of sig 0.00 < 0.05 or t table (5.275) > t arithmetic (2.051). So the simultaneous provision of punishment affects the achievement of learning outcomes for students in fiqh lessons at MTs Al-Fatah Ambon. (2). There is a positive and significant effect of giving rewards to students with the value of the results of the hypothesis test (t test) with a sig value of 0.03 <0.05 or t table (2.290) > t arithmetic (2.051). So giving rewards simultaneously affects the achievement of learning outcomes for students in fiqh lessons at MTs Al-Fatah Ambon.Keywords: Effect of punishment and reward, learning outcomesAbstrak: Tujuan penelitian ini adalah untuk mengetahui adakah pengeruh pemberian Punishment dan reward terhadap peningkatan hasil belajar peserat didik pada pelajaran fikih di MTs Al-Fatah Ambon. Penelitian ini menggunakan tipe penelitian kuantitatif, dilakukan selama satu bulan mulai dari tanggal 19 November 2020 samapai 19 Desember 2020. Populasi dalam penelitian yaitu seluruh peserta didik kelas VIII ( VIII1,VIII2,dan VIII3) dan sampel sebanyak 30 orang dari keseluruhan siswa di kelas VIII yang diambil dengan mengunakan teknik rondom sampling acak dengan skor penelitian mengunakan skala likert. Dalam mengukur instrumen peneliti mengunakan angket sebanyak 22 pernyataan yang dilakukan dengan mengunakan google from. Kemudian dilakukan pengujian dengan mengunakan uji validitas dan reliabilitas dengan bantuan SPSS versi 22. Setelah  diperoleh data dari hasil angket kemudian peneliti menganalisis data dengan uji linieritas dan normaliatas mengunakan bantuan SPSS versi 22. Variabel hasil belajar fikih berupa nilai ujian tengah semester tahun pelajaran 2019-2020. Teknik analisi data untuk menguji hipotesis peneliti mengunakan uji F. Hasil penelitian menunjukan bahwa; (1) Ada pengaruh yang positif dan signifikan pemberian punishment terhadap hasil belajar peserta didik dengan nilai hasil uji hipotesis (uji t)  dengan nilai sig 0,00 < 0,05 atau  t tabel (5,275) >  t hitung (2,051). Maka pemberian punishment secara simultan berpengaruh pada pencapaian hasil belajar peserta didik pelajaran fikih di MTs Al-Fatah Ambon. (2). Ada pengaruh yang posistif dan signifikan pemberian Reward terhadap peserta didik dengan nilai hasil uji hipotesis (uji t)  dengan nilai sig 0,03 < 0,05 atau  t tabel (2,290) > t hitung (2,051). Maka pemberian reward secara simultan berpengaruh pada pencapaian hasil belajar peserta didik pelajaran fikih di MTs Al-Fatah Ambon.